2013
DOI: 10.1371/journal.pone.0071313
|View full text |Cite
|
Sign up to set email alerts
|

Rural/urban Background, Depression and Suicidal Ideation in Chinese College Students: A Cross-Sectional Study

Abstract: ObjectivesThe objective of this study was to examine, first, the relationship of having a rural vs. urban background with suicidal ideation in Chinese college students, and second, whether a potential relationship was mediated by depression.MethodsA survey was conducted among 1,145 undergraduate students at a university in China. Suicidal ideation and depressive symptoms were measured by the revised Hopkins’ Symptom checklist (SCL-90-R). Associations between rural vs. urban background, depression and suicidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 38 publications
2
28
2
4
Order By: Relevance
“…Undergraduates with an urban household registration reported higher suicidality compared to those with a rural household registration. This is in contrast with an earlier study which indicated no difference in the suicidality levels between rural and urban Chinese college students [42], or higher levels of suicidality among rural Chinese college students [10]. The findings may reflect the narrowing of rural:urban ratios in suicide rate, which has traditionally been higher among the rural Chinese [43].…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Undergraduates with an urban household registration reported higher suicidality compared to those with a rural household registration. This is in contrast with an earlier study which indicated no difference in the suicidality levels between rural and urban Chinese college students [42], or higher levels of suicidality among rural Chinese college students [10]. The findings may reflect the narrowing of rural:urban ratios in suicide rate, which has traditionally been higher among the rural Chinese [43].…”
Section: Discussioncontrasting
confidence: 98%
“…There is a collective body of evidence on the identification of risk and protective factors for suicide, which includes factors such as life stress and coping style [8], personality factors of impulsivity and aggression [9], and depression [9][10][11][12]. In addition, adverse developmental influences or events such as childhood adversity, divorce of parents, loss of a parent, and sexual abuse are also risk factors for increased suicidality [9][10][11][12]. Among Chinese college students, factors that have been found to influence suicidality are academic performance, academic stress, occupational future, recent conflicts with classmates, satisfaction with major, and the rupture of romantic relationships [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that depression was more prevalent among students from rural area. This finding was similar to a previous study conducted in China, among college students 28 . The positive association between rural background and depression may be due to the fact that students from rural areas are more likely to have had poor family environments and considered as having a lower social status 28 .…”
Section: Discussionsupporting
confidence: 92%
“…Questionnaire on factors associated with depression : The information on the risk and protective factors for depression was obtained using a structured pretested questionnaire. This risk and protective factors questionnaire was specifically designed for this study, based on the literature review 5 6 7 18 19 20 21 22 23 24 25 26 27 28 29 30 . Opinion of the experts was obtained to increase its face validity and repeatability was tested by confirming test-retest hypothesis.…”
Section: Methodsmentioning
confidence: 99%
“…Sin embargo, estas cifras son considerablemente mayores que las señaladas en investigaciones realizadas en adolescentes de regiones urbanas; en Tailandia la ideación suicida es del 8,8 % (36), y en Francia, del 16 % (4). Al respecto, hay resultados diversos: mientras algunos hallazgos no muestran una asociación significativa de la ideación suicida con la residencia urbana o rural de los adolescentes (37), otros señalan que los del área rural exhiben mayor prevalencia que sus pares del área urbana, con diferencias significativas (38).…”
Section: Discussionunclassified